Joint learning of feature and topology for multi-view graph convolutional network - Chen, Yuhong; Wu, Zhihao; Chen, Zhaoliang; Dong, Mianxiong; Wang, Shiping (Neural Networks, 2023)
Graph convolutional network has been extensively employed in semi-supervised classification tasks. Although some studies have attempted to leverage graph convolutional networks to explore multi-view data, they mostly consider the fusion of feature and topology individually, leading to the underutilization of the consistency and complementarity of multi-view data. In this paper, we propose an end-to-end joint fusion framework that aims to simultaneously conduct a consistent feature integration and an adaptive topology adjustment. Specifically, to capture the feature consistency, we construct a deep matrix decomposition module, which maps data from different views onto a feature space obtaining a consistent feature representation. Moreover, we design a more flexible graph convolution that allows to adaptively learn a more robust topology. A dynamic topology can greatly reduce the influence of unreliable information, which acquires a more adaptive representation. As a result, our method jointly designs an effective feature fusion module and a topology adjustment module, and lets these two modules mutually enhance each other. It takes full advantage of the consistency and complementarity to better capture the more intrinsic information. The experimental results indicate that our method surpasses state-of-the-art semi-supervised classification methods. •Propose an end-to-end framework for multi-view semi-supervised classification.•Design a multi-view auto-encoder to fuse feature by approximating the matrix decomposition.•Explore a more robust topology that fuses the adjacency matrices generated by kNN and kFN.